2015
DOI: 10.1099/ijsem.0.000392
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium ecuadorense sp. nov., an indigenous N2-fixing symbiont of the Ecuadorian common bean (Phaseolus vulgaris L.) genetic pool

Abstract: Rhizobium ecuadorense sp. nov., an indigenous N 2 -fixing symbiont of the Ecuadorian common bean (Phaseolus vulgaris L.) genetic pool

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 36 publications
2
17
0
2
Order By: Relevance
“…Although few studies have reported on the genetic diversity of Rhizobium in Ecuador (Ribeiro et al, 2013), this is the first report of species diversity in the southern region of the country. Similar to this study, R. etli, R. leguminosarum and R. tropici have been previously isolated from common bean nodules (Martínez-Romero, 2003;Aguilar;Riva;Peltzer, 2004;Oliveira et al, 2011) and are considered to be the predominant occupant species of bean nodules in the Andean region (Junier et al, 2014;Ribeiro et al, 2015). Ecuador, north of Peru, Colombia and the Andean Region are currently considered to be the centers of domestication/diversity of the common bean (Oliveira et al, 2011).…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Although few studies have reported on the genetic diversity of Rhizobium in Ecuador (Ribeiro et al, 2013), this is the first report of species diversity in the southern region of the country. Similar to this study, R. etli, R. leguminosarum and R. tropici have been previously isolated from common bean nodules (Martínez-Romero, 2003;Aguilar;Riva;Peltzer, 2004;Oliveira et al, 2011) and are considered to be the predominant occupant species of bean nodules in the Andean region (Junier et al, 2014;Ribeiro et al, 2015). Ecuador, north of Peru, Colombia and the Andean Region are currently considered to be the centers of domestication/diversity of the common bean (Oliveira et al, 2011).…”
Section: Resultssupporting
confidence: 77%
“…The analysis of natural bean populations has led to the proposal of two major centers of diversification: the Mesoamerican center (Mexico, Central America and Colombia) and the Andean center (Ecuador, Peru and Bolivia) (Beebe et al, 2001;Junier et al, 2014). However, the genetic diversity of rhizobianodulating beans in Ecuador is, for the most part, unknown (Ribeiro et al, 2015). In previous studies, Bernal and Graham (2001) and Ribeiro et al (2013) reported on the diazotrophic rhizobial communities in soils of northern and central Ecuador.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Posteriormente, se ha identificado una diversidad amplia de linajes de rizobios de los nódulos de Phaseolus vulgaris con análisis tanto moleculares (Miranda-Sánchez et al, 2016;Ribeiro et al 2013;Wang et al, 2011) como genómicos en distintas regiones de México, del Caribe (Carrascal et al, 2016;Díaz-Alcántara et al, 2014;Santamaría et al, 2017;Tong et al, 2018) y de China, donde el frijol fue introducido y es cultivado a gran escala (Cao et al, 2014). Se han reclasificado a algunas cepas previamente consideradas como R. etli en otras especies cercanas, R. phaseoli (Ramírez-Bahena et al, 2008), R. ecuadorense (Ribeiro et al, 2015) y R. esperanzae (Cordeiro et al, 2017), mientras otros linajes nuevos no han sido todavía nombrados como nuevas especies (López-Guerrero et al, 2012). Es notable que distintas especies de rizobios con capacidad de formar nódulos en P. vulgaris comparten un plásmido simbiótico conservado que representa al simbiovar phaseoli o tropici, lo que indica que los plásmidos pueden transferirse entre rizobios en condiciones naturales (Cao et al, 2014), y se ha confirmado en experimentos de laboratorio (Brom et al, 1988;Martínez et al, 1987;Rogel et al, 2001).…”
Section: Rizobios Encontrados En Méxicounclassified